Analysis of the Effect of Occupational Therapy on Post-Stroke Patient Recovery: Impacts on Motor Skills, Cognitive Function, and Emotional Well-Being - Esniwati, Elpria (Institute of Accounting Research and Novation (IARN), 2024)
This study investigates the impact of occupational therapy on the recovery of post-stroke patients, focusing on improvements in motor skills, cognitive function, emotional well-being, and overall quality of life. A total of 100 stroke survivors were randomly assigned to either an occupational therapy intervention group or a control group receiving standard care. The intervention comprised individualized, task-oriented therapy over six months, addressing motor, cognitive, and emotional impairments. Outcomes were measured using standardized assessments, including the Fugl-Meyer Assessment, Barthel Index, Montreal Cognitive Assessment (MoCA), and Beck Depression Inventory (BDI). Additionally, qualitative interviews provided insights into patient experiences and therapy impacts. The occupational therapy group showed significant improvements in motor skills, as evidenced by higher scores on the Fugl-Meyer Assessment and increased functional independence as measured by the Barthel Index. Cognitive function improved markedly, with higher MoCA scores observed in the intervention group. Emotional well-being also enhanced, with reduced depressive symptoms reported on the BDI. Qualitative data revealed increased patient satisfaction, autonomy, and a more positive outlook on recovery. Occupational therapy is effective in promoting recovery for stroke survivors, leading to notable improvements in motor function, cognitive abilities, and emotional health.